Pakistan : Beyond the 'Crisis State' - Edited by Maleeha Lodhi (Karachi Oxford University Press, 2012)
The editor is the former Pakistan Ambassador to both the United States and the United Kingdom, and for this book she has gathered together contributors to discuss the state of Pakistan. This collection goes against the grain to argue that the future for Pakistan's democracy looks bright. It brings together an extraordinary array of experts, including renowned Pakistani journalist Ahmed Rashid, Pakistani American sociologist and historian Ayesha Jalal, and Zahid Hussain, author of several books on Islamic militancy in Pakistan. It takes stock of the Islamic republic's fundamental strengths and weaknesses. Presenting a picture of the nation as understood by its people, this anthology assesses the political, economic, social, and foreign policies of an embattled government and its institutional challenges. Ambassador Akbar Ahmed, chair of Islamic studies at American University, and Munir Akram, Pakistan's former ambassador to the United Nations, provide critical perspectives on Pakistan's future. Additional essays capture the complex interplay between domestic and external pressures, such as the variety of powers that continue to manipulate the country's behavior and outcomes. The contributors gathered here ultimately conclude that Pakistan is capable of transitioning into a stable modern Muslim state, though bold reforms are necessary. Offering a detailed and balanced agenda for such reform, Pakistan takes a bold step in reeling the country back from the brink of crisis.
Include Abbreviations, Notes, References and Index.
Keywords: Pakistan -- Politics and government -- Diplomatic relations -- Strategic aspects of individual places -- Social conditions -- Economic history -- Economic policy -- Education